Pengaruh Potongan Harga (Price Discount) Dan In Store Display Terhadap Kepuasan Pelanggan: Studi Kasus Pada Pelanggan Rizky Net Bandar Masilam - Dede Jailani; Purba, Rakhmawati; Damanik, Sri Winda Hardiyanti (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2022)
The purpose of this study was to determine the effect of price discounts and in-store displays on customer satisfaction partially or simultaneously on Rizki Net Bandar Masilam customers with a type of quantitative descriptive approach. The method used is the census method in taking the population and sample. The results of the study can be concluded: (1) It can be seen that the value of the adjusted R square is 0.623 or 62.3%. This shows that In Store Display (X2) and Discounts (X1) can explain Customer Satisfaction (Y) of 62.3%, the remaining 37.7% (100% - 62.3%) is explained by other variables outside this research model. (2) The results of the (Partial) t test show that tcount (9.017) > ttable (2.011), and the significance value is 0.00 <0.05, so it can be concluded that the first hypothesis is accepted, meaning that the discount (X1) has a significant effect on Customer Satisfaction (Y). (3) The results of the t test (Partial) can be seen that tcount (3.500) > ttable (2.011), and the significance value is 0.00 <0.05 so it can be concluded that the third hypothesis is accepted, meaning that In Store Display (X2) has a significant effect on Customer Satisfaction (Y). (4) The results of the F test can be seen that Fcount (41.413) > Ftable (3.16), and a significance value of 0.000 <0.05, it can be concluded that the third hypothesis is accepted, meaning the Price discount variable (X1), the in store display variable ( X2) has a significant effect simultaneously (simultaneously) on the customer satisfaction variable (Y).